Bilah Berputar sebagai Media Pembelajaran Olah Tubuh untuk Melatih Gerak dalam Pengendalian Diri - Sarjiwo Sarjiwo (Institut Seni Indonesia Yogyakarta, 2021)
The Rotating Blades as the Learning Media of Body Exercise to Train Movement in Self-Control. This study aims to reveal how media (blades) becomes the learning media of body exercises to train motion in self-control. This research is experimental research by giving treatment to research subjects. The treatment was carried out in three stages: (1) The study subjects adapted to the blades moving freely for 2 minutes; (2) the research subjects improvised motion freely while rotating the blades for 2 minutes; and (3) the research subjects improvised movement freely while turning the blades consciously to control themselves for 2 minutes. The motion process in the first, second, and third treatments was observed as the data for analysis. The observation was conducted by interviewing the research subjects. The results showed that in the first treatment, the blades that the research subjects rot hit the body, hitthe floor, and slack ropes accumulated twelve times. In the second treatment, the research subjects rotated the blades hitting the body, hitting the floor, and the slack ropes were cumulatively 21 times. And in the third treatment, the blades were rotated by the research subjects hitting the body, hitting the floor, and the slack ropes accumulated seven times. The research results indicate that if the free movement is not controlled, the possibility of an accident is more significant (21 times). Meanwhile, if the movement is controlled, the case of an accident is more minor (7 times).Keywords: rotating blade; body exercise; self-control